Time Pressure, Educational Skills, and Autonomy as Predictors of Job Satisfaction and Job Performance: The Moderating Role of Internet Usage among Ministry of Maritime Affairs and Fisheries Employees, Indonesia - Afzil Ramadian; Loso Judijanto; Encep Sopandi (Fundamental and Applied Management Journal, 2026)
This research looks at how time pressure, learning abilities, and freedom at work influence how satisfied employees are with their jobs and how well they perform in their roles within Indonesia's Ministry of Maritime Affairs and Fisheries. It also looks at how internet use affects the association between these factors and job satisfaction. A quantitative correlational design was employed in this investigation. Data were gathered from 153 employees who were chosen using purposive sampling and were examined using SmartPLS 3 and partial least squares structural equation modeling (PLS-SEM). The results indicate that time pressure and autonomy were important factors in determining job satisfaction, but educational skills did not have a meaningful impact on job satisfaction at the 5% significance level. Time pressure, knowledge of education, ability to work independently, and how happy someone is with their job all had a big effect on how well they perform at work. Using the internet has greatly reduced how much time pressure, learning abilities, independence, and happiness at work are connected to each other. The model accounted for 63% of the difference in contentment at work and 71% of the variation in job performance. The results show that factors like time pressure, freedom to make decisions, how well someone can learn, and how happy they are with their job all play a big role in how well employees perform. The way people use the internet helps to strengthen the connection between important work factors and how satisfied they are with their job, but it doesn't directly influence that connection. These results show that having helpful digital tools can make a big difference in making employees happier and more effective in government workplaces.